Review of sandwich structures under impact loadings: Experimental, numerical and theoretical analysis - Guo, Haoyuan; Yuan, Hui; Zhang, Jianxun; Ruan, Dong (Thin-walled structures, 2024)
•This paper reviews investigations on energy absorption and dynamic response of sandwich structures over the past few decades.•The impact loading includes low-velocity impact, explosive loading as well as ballistic impact.•Core configurations of sandwich structures include metal foam and polymer foam, ungraded and graded honeycomb, auxetic honeycomb and foam inserted honeycomb, corrugated core and foam inserted corrugated core, truss core, undrilled and drilled I-core, and Y-shaped core.•The excellent characteristics concerning load resistance and energy absorption of sandwich structures can guide their application in engineering practice. With the swift advancement of aerospace, shipbuilding and engineering, the significance of sandwich structures with cellular cores is becoming increasingly prominent due to their multi-functional and lightweight attributes. In addition, impact loadings are very common in the engineering practice and may potentially cause significant adverse impact on products and equipment. Emerging manufacturing technologies facilitate the fabrication of high quality sandwich plates with improved stiffness and strength to withstand impact loadings. Therefore, extensive investigations have been conducted on sandwich structures under various impact loadings. This paper provides a comprehensive review of the valuable experimental, analytical, and numerical investigations conducted on the dynamic response of sandwich structures spanning several decades. The paper aims to reveal the underlying deformation mechanisms governing the response of sandwich structures subject to impact loadings. The focus is primarily on popular sandwich structures, such as beams, plates, and curved plates, under low-velocity impact, blast loading, and ballistic impact. Various core configurations of sandwich structures are explored, including metal and polymer foams, uniform and graded honeycombs, auxetic honeycombs, foam inserted honeycombs, corrugated core and foam inserted corrugated core, truss core, undrilled and drilled I-core, chiral core, star-shaped core and Y-shaped core. Current challenges and recommendations for future work have also been articulated.